Phycocyanin Ameliorates Radiation‐Induced Acute Intestinal Toxicity by Regulating the Effect of the Gut Microbiota on the TLR4/Myd88/NF‐κB Pathway. Issue 7 (25th November 2019) - Lu, Lina; Li, Wenjun; Sun, Chao; Kang, Shuhe; Li, Jia; Luo, Xingping; Su, Qiong; Liu, Bin; Qin, Song
Abstract: Background: Radiation‐induced gastrointestinal syndrome, including nausea, diarrhea, and dehydration, contributes to morbidity and mortality after medical or industrial radiation exposure, which seriously affects patient quality of life after treatment. No safe and effective radiation countermeasure has been approved for clinical therapy. In this study, we aimed to investigate the potential protective effects of phycocyanin (PC) against radiation‐induced acute intestinal injury. Materials and Methods: C57BL/6 mice were orally administered 50 mg/kg PC once per day for 1 month before exposure to total‐abdominal x‐ray irradiation at a single dose of 12 Gy. The effects of PC on intestinal histopathology and integrity, gut microbiota, lipopolysaccharides (LPS), inflammatory cytokines, and Toll‐like receptor 4 (TLR4)/myeloid differentiation factor 88 (Myd88)/nuclear factor κB (NF‐κB) signaling were evaluated. Results: Severe histopathological damage, such as intestinal mucosal epithelial cell apoptosis, necrosis, and nuclear rupture, was most clearly observed 24 hours after total‐abdominal x‐ray irradiation. Intestinal integrity was damaged by irradiation, which manifested in reduced levels of the tight‐junction proteins Claudin‐1, Occludin, and zonula occludens‐1(ZO‐1). PC pretreatment significantly ameliorated radiation‐induced intestinal injury. PC also modulated the gut microbiota composition, increasing the proportion of beneficial bacteria and decreasing that of harmful bacteria, which in turn lowered LPS levels and suppressed TLR4/Myd88/NF‐κB pathway activation. Finally, levels of corresponding inflammatory cytokines, including tumor necrosis factor α and interleukin‐6, were also downregulated. Conclusion: PC protects against mouse intestinal injury from high‐dose radiation by regulating the effect of the gut microbiota on the TLR4/Myd88/NF‐κB pathway, suggesting PC as a promising natural radiation countermeasure.